"Living end: future of death, aging and immortality" - "Brown, Guy" (London, 2008)
Death is not what it once was. The decline of acute death by infections, starvation, violence and heart attack has allowed people to reach extreme old age but ushered in disability, dementia and degenerative disease, with profound consequences for the self and society. The future of death is even more extreme, and constitutes one of the greatest challenges of the 21st century. In chapters echoing Dante's nine circles of hell, Dr Guy Brown explores these vital issues at various levels, from the cell, to the whole body, to society. He reveals that cell death is central to cutting edge biology and medicine from embryo formation to cancer cures. He tracks the seismic shifts in the causes and character of death that are rocking medicine. And reveals how technological innovations, such as cloning and electronic interfaces, hint at new modes of survival after death.